OR2W3 sequence variants are unlikely to cause inherited retinal diseases. (1st October 2016) - Sharon, Dror; Kimchi, Adva; Rivolta, Carlo
ABSTRACT: Because of its formidable throughput, whole exome sequencing (WES) is significantly increasing the power of investigations in ophthalmic genetics. However, when applied to Mendelian conditions, WES results often contain many false positives, e.g. candidate mutations that are unrelated to the disease. For instance, highly polymorphic genes such as olfactory receptor genes carry a plethora of both common and rare alleles that are part of the normal set of variations of the human genome. Following a WES-based study, the heterozygous missense variant p.R142W in the olfactory receptor gene OR2W3 was recently reported as a pathogenic mutation causing autosomal dominant retinitis pigmentosa (RP). This variant, however, was not scored against data contained in public WES repositories, indicating that p.R142W is present in ~1 in 6500 control individuals. Therefore, if it really was pathogenic, it would be responsible for a percentage of dominant RP cases corresponding to the double of those recorded so far worldwide, or 2/3 of all RP cases (dominant, recessive, and X-linked). We therefore conclude that this sequence variant, and hence the OR2W3 gene, do not cause RP. Prompted by these findings and based on simple principles of population genetics, we suggest that WES studies should consider DNA variants as the possible cause of dominant RP only if they are present in less than 1:100, 000 individuals from the general population. In addition, we propose that DNA variants belonging to highly polymorphic genes should be carefully analyzed at the functional level before inferring their pathogenicity, in RP or other genetic diseases.